1974
DOI: 10.1113/expphysiol.1974.sp002266
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Blood Pressure in the Unanaesthetized Fetal Lamb After Changes in Fetal Blood Volume and Haematocrit

Abstract: Fourteen sheep fetuses in the third trimester of gestation were surgically prepared with intravascular catheters and five were nephrectomized. All experiments were done on unanaesthetized fetuses in utero, 3 to 9 days after surgery. Mean arterial blood pressure was recorded while fetal blood volume was changed by injection or withdrawal of blood, or infusion of Ringer's or dextran solutions. Fetal arterial blood gases and pH changed little during the experiments and were shown not to have affected the results.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
2

Year Published

1978
1978
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 15 publications
(28 reference statements)
2
11
2
Order By: Relevance
“…Baroreflex mechanisms could not be shown to moderate these changes. The fetal blood volume per unit weight is high (Creasy, Drost, Green & Morris, 1970), and blood volume is an important determinant of fetal blood pressure and placental blood flow (Faber & Green, 1972;Faber et al 1974). Vatner, Boettcher, Hendryx & McRitchie (1975) have shown in the conscious dog that volume loading results in a decrease of baroreflex sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Baroreflex mechanisms could not be shown to moderate these changes. The fetal blood volume per unit weight is high (Creasy, Drost, Green & Morris, 1970), and blood volume is an important determinant of fetal blood pressure and placental blood flow (Faber & Green, 1972;Faber et al 1974). Vatner, Boettcher, Hendryx & McRitchie (1975) have shown in the conscious dog that volume loading results in a decrease of baroreflex sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…1969;Ponte & Purves, 1973) but it is not clear if the baroreceptors are active in utero in the absence of endocrine and other changes induced by operation. Faber et al (1974) calculated the open-loop gain of the baroreflex of fetal lambs in utero to be zero. They altered blood pressure by varying the blood volume and found that arterial and central venous pressures and heart rate increased when the blood volume was increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, others [6] using similar methods have contended that the baroreflex does not operate at resting arterial pressures in a normal fetus in utero. Fetal responses to hemorrhage have sup ported the presence of functional baroreflexes [2] but this too is controversial [7], This study examined responses to arterial hypotension in fetal and newborn lambs. Few studies have examined fetal cardiovascular responses to reductions of arterial pressure and these have provided conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…The regulation of blood pressure is mainly influenced by autoregulation, the autonomic nervous system and the humoral system, but the placenta (uteroplacental circulation) is not capable of autoregulation [49]; it appears to be totally dependent on perfusion pressure. Although the autonomic nervous system in the fetus develops with advancing gestation, fetal end organ response to the autonomic nervous system (in both blood vessels and the heart) is of a much smaller magnitude than the adult response [50,51]. Blood pressure homeostasis may be more important in the fetus than in the adult, as it determines the level of placental perfusion which then determines the extent of respiratory gas exchange.…”
Section: A Mechanisms Of Onset Of Labor and Transient Diabetes Insipmentioning
confidence: 99%